Cleft Repair in Adults: A Report on a Case Series. (August 2018) - Fuller, Jennifer; Drake, David; Felstead, Andrew; Colbert, Serryth
Speech defects and facial appearance due to untreated cleft lip and/or palate in the elderly population have associated life-long impacts on the quality of life for these patients. Treatment and rehabilitation in this patient group can be extensive and the problems not easily corrected. We report the outcomes of surgical repair of cleft in a series of elderly patients with unrepaired cleft lip and/or palate. Our results confirm an improvement in speech, quality of life and aesthetic outcomes after surgical repair in these patients. With this in mind, we advise cleft teams to consider surgical repair of untreated cleft lip and/or palate in the elderly population.